Descriptive List of Mutiny Papers : In the National Archives of India, Bhopal (Vol. VIII) - Islam, Muzaffar-e, (Brill | Manohar Publishers & Distributors, 2020)
The collection of 'Mutiny Papers' housed in the National Archives of India, Regional Office, Bhopal is an invaluable historical resource on the uprising of 1857 in India, particularly in the Bundelkhand region and in Central India. These are 10,000 documents in Persian, spread over 425 files. The book, VIIIth in the series, presents a word-for-word translation of the documents from 90 files. The events of 1857 upon which these documents throw light, are the siege of Gwalior by the insurgents and its recapture by the British forces and reinstallation of Maharaja Sindhia, fall of Rani of Jhansi, and the capture of Jhansi by the British. Besides, there is an eye-witness account of Delhi, from day one when the so-called mutineers arrived in Delhi from Meerut and started indiscriminate killing of the British. Delhi was recaptured subsequently. Nawwab Sikandar Begam, the then Nawwab of Bhopal State was one of those who remained loyal to the British Government. Her loyalty saved her small State from any turmoil. While the other States like Jhansi, Awadh, Banda, Farrukhabad, Kanpur, etc., were completely ruined and captured by the British forces. Delhi, the stronghold of the Mughal Empire was fully devastated and captured. Bahadur Shah Zafar, the last Mughal King was exiled to Rangoon after the victory of the British forces and India became part of the British Empire afterwards.